2015
DOI: 10.1016/j.ijid.2014.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospital-acquired infections with multidrug-resistant bacteria in an oncology intensive care unit

Abstract: The emergence of MDR bacteria poses a difficult task for physicians, who have limited therapeutic options. Critically ill cancer patients admitted to the ICU are at major risk of a bacterial MDR-HAI that will impact adversely on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
4
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 24 publications
10
111
4
5
Order By: Relevance
“…5 A maior frequência neste estudo dos microrganismos Acinetobacter baumanni e Pseudomonas aeruginosa resistentes aos carbapenêmicos, e Staphylococcus aureus resistentes à oxacilina foi similar ao observado em estudos no Brasil e América Latina. 3,9,12 Na América Latina e Brasil, conforme os dados do SENTRY, os bastonetes Gram negativos (BGN) não fermentadores (Acinetobacter spp. e Pseudomonas aeruginosa) multirresistentes e as Enterobacteriaceae produtoras de betalactamases de espectro ampliado (ESBL) constituem o principal problema de farmacorressitência.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…5 A maior frequência neste estudo dos microrganismos Acinetobacter baumanni e Pseudomonas aeruginosa resistentes aos carbapenêmicos, e Staphylococcus aureus resistentes à oxacilina foi similar ao observado em estudos no Brasil e América Latina. 3,9,12 Na América Latina e Brasil, conforme os dados do SENTRY, os bastonetes Gram negativos (BGN) não fermentadores (Acinetobacter spp. e Pseudomonas aeruginosa) multirresistentes e as Enterobacteriaceae produtoras de betalactamases de espectro ampliado (ESBL) constituem o principal problema de farmacorressitência.…”
Section: Discussionunclassified
“…1,2 Nas instituições hospitalares, as Unidades de Terapia Intensiva (UTI) são consideradas o epicentro da resistência bacteriana devido à maior ocorrência de surtos por bactérias multirresistentes. [3][4][5] Nas UTIs as taxas de infecções são estimadas entre 18 e 54%, sendo responsável por 5 a 35% de todas as IRAS e por, aproximadamente, 90% de todos os surtos hospitalares. [6][7][8] Em tais unidades os pacientes colonizados e/ou infectados representam a principal fonte de patógenos pois, na colonização apesar de não haver sintomas clíni-cos e imunológicos de infecção, os microrganismos estão presentes nas superfícies cutâneas e mucosas do hospedeiro.…”
Section: Introductionunclassified
“…12 The hospital-acquired infections manifest in a wide gamut of severe clinical ramifications, such as bacteremia, septic shock, ventilator-related pneumonia and massive soft tissue necrosis, and rapidly progress to systemic infections that eventually culminate in multiorgan failure and death. 13 The control measures including implementation of hygiene, patient isolation and environmental decontamination have proved ineffective in keeping the infection at bay. Improper use of antibiotics has favored an upward trend in the development of resistance to almost all the available drugs, further compounding the clinical problem.…”
Section: Gravity Of the Problemmentioning
confidence: 99%
“…However, depending on patient demographics and the strains present, the proportion of certain infections caused by A. baumannii can be much larger than 5 to 10%. For example, a retrospective study of ICU-acquired infections in the ICU of the National Cancer Institute of Mexico reported that A. baumannii was the causative agent of 6% of total hospital-acquired infections but disproportionately represented 60% of pneumonia and 25% of bloodstream infections (7). A. baumannii has rapidly evolved into a difficult-to-treat pathogen through acquisition, mostly via integrons and transposons, of multiple drug resistance genes that supplement the already high level of intrinsic drug resistance (8).…”
mentioning
confidence: 99%